A Reliability Generalization Meta-Analysis of the Creative Achievement Questionnaire - YÖRÜK, SÜREYYA (My University, 2022)
The Creative Achievement Questionnaire (CAQ) is widely used to measure the creative achievement levels of individuals. Previous studies reported a varying range of reliability coefficients for the CAQ. To this date, no study has investigated the variability in the reliability coefficients of the CAQ. A random-effects reliability generalization meta-analysis, heterogeneity analyses, and moderator analyses were conducted in the present study to examine the variability in the reliability coeffi-cients. The mean alpha value for the total CAQ score was estimated to be .765 (95% CI: .708-.811). The Q test (Q(33) = 1716.648, p < .0001) and I2 (98.74%) values denoted statistically significant heterogeneity among the alpha coefficients. These findings indicate that reliability is a property of CAQ scores and that the reliability of scores changes significantly across samples. The moderator analyses showed that the reliability coefficients were not impacted by the moderator variables considered in this study. However, certain moderator variables that were not included in the analyses may have impacted the reliability coefficients. The findings of the present study imply that the CAQ can be used for exploratory research.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sanat; Social Sciences and Humanities; Psychology; Developmental Psychology; Art; Temel Bilimler (SCI); Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; PSİKOLOJİ, GELİŞTİRME; SANAT; Natural Sciences (SCI); Arts & Humanities (AHCI); PSYCHOLOGY; ARTS & HUMANITIES; PSYCHOLOGY, DEVELOPMENTAL; ART; Gelişim ve Eğitim Psikolojisi; Sosyal Bilimler ve Beşeri Bilimler; Görsel Sanatlar ve Gösteri Sanatları; Psikoloji (çeşitli); Developmental and Educational Psychology; Social Sciences & Humanities; Visual Arts and Performing Arts; Psychology (miscellaneous)